Suklastota istorija: sovietų totalitarizmas ir partizanų karo prisiminimas - Gailius, Bernardas (Lietuvos istorijos studijos, 2008)
The historiography of the Lithuanian guerrilla war of 1944–1953 is usually considered to be wide. However, the same may not be applied to the integration of the guerrilla war into the historical culture of contemporary Lithuania. The variety of opinions and interpretations indicates that there exists no traditional understanding of the war. That also makes it impossible for any of the positions to be regarded as "critical" or "revisionist," as there is nothing to revise or criticize. This feature makes the guerrilla war exceptional among most historical events and requires some scientific explanation. The purpose of this article is to find one.The term "historical culture" was formulated by the German historian Jėim Riisen. It defines the role of history in organizing the worldview of society and forming its identity. Therefore, historical culture includes all stages of history telling and writing—from family to university. The key element of historical culture is historical narrative. J. Riisen distinguishes four types of narratives: the traditional narrative, the exemplary narrative, the critical narrative, and the genetic narrative. The interaction of these types of narratives defines the dynamics of historical culture. After some important historical event, the traditional and the exemplary narratives come first. They incorporate the event into the historical tradition of society. Later, the critical narratives appear that challenge the tradition. Finally, the genetic narratives help to grasp the changes in the tradition itself.This scheme does not work with the Lithuanian guerrilla war of 1944–1953. The systematic Soviet repressions were aimed at the complete destruction of the Lithuanian social pattern. They prevented the traditional and the exemplary narratives from appearing. There were some stories and memoirs of the guerrilla fighters and their supporters, but these did not spread because of terror. People were silenced and then introduced to the Soviet narrative, which may only be defined as quasi-historical because it was a part of the propaganda. Imitating the "popular" and the "scientific" approaches, the Soviet regime spread its narrative and constructed the quasi-historical culture, which was itself a part of the "fictitious world of stability," as the philosopher Hannah Arendt described it. This way, the Lithuanian society was forced to live with fake history.After the restoration of Lithuanian independence in 1990, the Soviet quasi-historical culture collapsed together with the regime. However, the damage was already done. The real historical culture did not form. This circumstance explains the absence of the traditional interpretation of the guerrilla war. It also indicates that the restoration of independence was also the renewal of the trauma caused by the Soviet repressions. Therefore, the Lithuanian historical culture has a "black hole," which needs to be filled if society means to return to normal life.There were efforts to restore the so-called "historical justice." But these were merely of political or judicial character. There were laws passed that provided justification for the guerrilla fighters' status. There were also criminal cases initiated against Soviet secret agents and collaborators. However, these efforts did not help the tradition to evolve, as they were not accepted by society. Therefore, it is argued in this article that historical studies should now play their part. The historical studies do not come from the "structures of power" but from the inside of society. They could more fruitfully trigger discussions and help to find some reasonable common points. This way, the traditional interpretation of the guerrilla war could be slowly built, and the historical culture would regain its normal dynamics.